Pengembangan Media Dan Bahan Ajar Digital Jenjang Sekolah Dasar Untuk Pemerolehan Literasi Dasar Anak Anak Indonesia Non Dokumen Di Malaysia - Dede Trie Kurniawan; Yunus Abidin; Yeni Yuniarti; Rendi Restiana Sukardi; Dinie Anggraeni Dewi (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Education for children of Indonesian citizens (WNI) who do not have residence documents in Malaysia is a critical issue that needs attention by the government. Children of Indonesian citizens who do not have legal educational documents are constrained from obtaining their rights to education in Malaysia. One form of attention given by the government is to provide educational services for all citizens, including Indonesian migrant workers in Malaysia through the Rumah Kita program and Indonesian learning studios in Malaysia. And based on information, the number of non-formal educators is still limited, both in terms of qualifications and competence. This research was conducted with the aim of developing digital media and teaching materials oriented to gamification and learning independence for non-document Indonesian children in Malaysia. The research method used is Design and Development (D&D) using the ADDIE model. At the development stage, the Multimedia Prototype learning media has feasibility that is validated by experts. This research was conducted by producing a reference digital learning resource for the fulfillment of non-documentary basic literacy of Indonesian children in Malaysia. The subjects for assessing media and learning resources were three expert lecturers consisting of elementary school literacy experts, media experts, and elementary school learning content experts. In this paper, researchers will reveal the level of feasibility of media and digital learning resources for non-documented Indonesian children in Malaysia. The three experts who were the subject of the evaluation of the products developed in general stated that these digital media and learning resources were appropriate and good for use in fulfilling the basic literacy of non-document Indonesian children in Malaysia, but there needed to be a forum in the form of a website that would be used as a form of well-administered learning resource center for each media and teaching materials.